2015
DOI: 10.1371/journal.pone.0132072
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification and In Vitro and In Vivo Validation of Anti-Psychotic Drug Fluspirilene as a Potential CDK2 Inhibitor and a Candidate Anti-Cancer Drug

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide. Surgical resection and conventional chemotherapy and radiotherapy ultimately fail due to tumor recurrence and HCC’s resistance. The development of novel therapies against HCC is thus urgently required. The cyclin-dependent kinase (CDK) pathways are important and well-established targets for cancer treatment. In particular, CDK2 is a key factor regulating the cell cycle G1 to S transition and a hallmark for cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…Among all the CDKs, CDK2 was identified as a key kinase in tumorigenesis and proliferation in a range of cancer types including lung cancer, liver cancer, colon cancer and breast cancer [11], [12], [13]. In this study, we identified CDK2 expression was significantly elevated in glioma tumor especially in GBM and was functionally required for GBM cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Among all the CDKs, CDK2 was identified as a key kinase in tumorigenesis and proliferation in a range of cancer types including lung cancer, liver cancer, colon cancer and breast cancer [11], [12], [13]. In this study, we identified CDK2 expression was significantly elevated in glioma tumor especially in GBM and was functionally required for GBM cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Another study showed that inhibition of CDK2 kinase activity reduced tumor proliferation via selectively targets the CD44 + /CD24 −/Low stem-like cells in triple-negative breast cancer when combined with conventional chemotherapy [11]. Additionally, a newly published study demonstrated that CDK2 inhibitor exhibits anti-cancer effect in human hepatoma HepG2 and Huh7 cells and significantly inhibited tumor growth [12]. Lim et al identified CDK2 as a direct therapeutic target of curcumin in colon cancer cells via cell cycle arrest in HCT116 cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the structures of 3,167 approved drugs were gathered from the ZINC database (28,29). To predict the binding conformations and the binding affinities of these drugs with the CDK4/6 proteins, the free and popular docking software idock v2.2.1 (20,21) was used to dock all of the compounds onto all of the CDK2/4/6 structures. Prioritized in accordance with the average predicted binding affinity, 9 commercially available compounds were identified, purchased and subsequently evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Using structure-based virtual screening via protein-ligand docking to select candidates from FDA-approved smallmolecule drugs, we previously identified two CDK2 inhibitors, adapalene (20) and fluspirilene (21). In the present study, we attempted to identify drugs with the ability to specifically inhibit both CDK4/6 at the same time without affecting CDK2.…”
Section: Discovery Of Rafoxanide As a Dual Cdk4/6 Inhibitor For The Tmentioning
confidence: 99%
“…Interestingly, we also have two drugs, Olmesartan, for hypertension, and Fluspirilene, for schizophrenia, from very different therapeutic areas in our shortlist. While no reports of their potential role in melanoma treatment have been found yet, numerous studies have suggested their applicability in different cancer treatments(Masamune et al, 2013;Abd-Alhaseeb et al, 2014;Shi et al, 2015;Patil et al, 2015).…”
mentioning
confidence: 99%